Sinergitas Guru Kristen Dan Orang Tua Siswa Dalam Penguatan Moderasi Beragama Di SMTK SoE - Adi Saingo, Yakobus; Leobisa, Jonathan; Ir. Koebanu, Dunosel (Jayapangus Press, 2024)
Religious pluralism in Indonesia is a characteristic inherent in its society, but behind it all there are still individuals and radical groups who try to divide the integrity of the nation by using religious issues incorrectly, therefore synergy between teachers and parents is needed students in instilling the values ​​of religious moderation. The aim of this research is to discuss the synergy of Christian teachers and parents in strengthening religious moderation at SMTK SoE. This research applies a qualitative method, where data is collected through interview activities using an FGD (Focus Group Discussion) approach with 10 Christian teachers and 10 parents of students. The information collected is reduced to an act of data analysis which explains the results that Christian teachers and parents can work together to strengthen religious moderation for the students/children they train so that the good values ​​for creating harmony can be embedded optimally. This awareness has also been implemented appropriately by Christian teachers and parents of students at SMTK SoE who have worked together to implement strengthening religious moderation based on indicators, namely: National commitment, non-violence, religious tolerance, and behavior that respects local traditions. Based on the explanations given by Christian teachers and students' parents, concrete forms of synergy in efforts to strengthen the values ​​of religious moderation can be identified, including: Teachers schedule meetings with students' parents on a regular quarterly basis to educate each other about the importance of developing the character of a tolerant life; Teachers have a WA group with parents so they use social media to motivate and supervise each other so that children can have ethical and moral behavior that respects others, without discriminating against their religious background; Parents play an active role by immediately reporting to teachers if any of their children begin to display religious extremism behavior; Parents and teachers participate directly in children's character education through school extracurricular activities, such as watching family films together, family gatherings, those based on religious tolerance, and so on; Furthermore, teachers and parents also work together in monitoring social media, online games and the shows consumed by students at home so that they do not fall into acts of violence seen on various existing digital media.